Three ways forward for CARI - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Looking for a compact organisation close to the ground that focuses on local development through a global approach using sustainable agriculture? The little-known French CARI (the centre for international action and results) could be a god-send. It...